2014
DOI: 10.5958/2394-4196.2014.00005.3
|View full text |Cite
|
Sign up to set email alerts
|

Lower incisor dentoalveolar compensation and symphysis dimensions in class II and class III patients

Abstract: Aim: The aim was to study and compare lower incisor dentoalveolar compensation and mandibular symphysis morphology of patients with Class II and Class III malocclusion. Materials and Methods: Lower incisor inclination (incisor mandibular plane angle [IMPA]), as well as buccal (LA) and lingual (LP) cortex depth, and mandibular symphysis height (LH) were measured in 60 lateral cephalometric X-rays of adult patients without prior orthodontic treatment. The subjects were divided into three groups based on antero-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…9 Implementation of cephalometric radiography in orthodontics has revolutionized the diagnosis, have been extraordinarily useful to in treatment planning procedures by allowing accurate valuations of skeletal and dental mal-relationships. 10 Several cephalometric analyses, 6,8 have been used to facilitate diagnosis by enabling accurate assessment of skeletal and dental relationships occurring in a different type of malocclusions.…”
Section: Introductionmentioning
confidence: 99%
“…9 Implementation of cephalometric radiography in orthodontics has revolutionized the diagnosis, have been extraordinarily useful to in treatment planning procedures by allowing accurate valuations of skeletal and dental mal-relationships. 10 Several cephalometric analyses, 6,8 have been used to facilitate diagnosis by enabling accurate assessment of skeletal and dental relationships occurring in a different type of malocclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Bangar et al [11] found that MS in Class III skeletal bases has reduced concavity on the labial surface and increased vertical dimension compared to Class I and Class II skeletal bases. Maniyar et al [17] also found that Class III skeletal base with retroclined incisors has taller MS. This is not in agreement with our result where our study indicates that MS variation in Class III skeletal base can be observed at the alveolar part, basal part, or both, where it varies from narrow and elongated or wide and short as mentioned previously.…”
Section: Discussionmentioning
confidence: 94%
“…Variation in MS morphology has been associated with individual variation [5], vertical facial proportions [5][6][7][8][9][10], sagittal skeletal relationship [11], incisor inclination [1,12,13], muscular and functional activities [4,14,15], and sexual dimorphism [3,16]. Studies on facial type and morphology of MS have mentioned that those with short face or forward growth of mandible has wider MS while those with long face or backward growth of mandible exhibits elongated and thin MS [8][9][10]17]. Moshfeghi et al [18] further emphasized that mandibular morphology is associated with the direction of mandibular growth.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the lower incisors has always been considered a major deciding factor in treatment planning and one of the key treatment objectives, to achieve the lower incisor stability. Several factors play a role in attaining lower incisor stability [4]. Numerous studies have proven that proclined lower incisors at the end of treatment, have always been considered an undesirable side effect of orthodontic treatment and is disadvantageous for two main reasons (1) it can lead to negative periodontal ramifications and (2) can result in reduced stability.…”
Section: Discussionmentioning
confidence: 99%
“…The position of lower incisor is key to achieve good facial aesthetics and have marked functional effects i.e., resisting incisor over eruption, providing harmony and functionality to TMJ, allowing appropriate anterior guidance and protrusive movements, to protect organic occlusion [1,2]. It has been proven that within dentofacial complex a compensatory mechanism exists that attempt to maintain a proportional and harmonious facial pattern, when either maxilla or mandible deviates from normal growth, then remaining orofacial structures responds to mask this discrepancy [3][4][5]. In this regard dental compensation acts as natural camouflage to sagittal and vertical discrepancies to achieve normal incisor relationship.…”
Section: Introductionmentioning
confidence: 99%